The influence of brand image, product quality, and trust on purchase intention for skintific moisturizers in Batam City - Stefenny Stefenny; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of brand image, product quality, and trust on consumer purchase intention toward Skintific moisturizer at PT X in Batam City. Employing a quantitative research design grounded in the positivist paradigm, data were collected from primary sources through structured questionnaires distributed to consumers. The total number of respondents was determined using a purposive sampling approach, and statistical analysis was conducted using multiple linear regression with the assistance of SPSS software to evaluate both partial (t-test) and simultaneous (F-test) effects. The empirical findings reveal that brand image exerts a positive and significant effect on purchase intention, indicating that a favorable perception of the brand—encompassing company reputation, product image, and user image—directly increases consumers’ willingness to buy. Product quality also shows a positive and significant influence, suggesting that the perceived excellence of the product’s safety, texture, efficacy, and performance enhances consumer interest. Likewise, consumer trust significantly and positively impacts purchase intention, demonstrating that confidence in the authenticity, reliability, and integrity of the product fosters higher purchasing motivation. Moreover, the simultaneous test results confirm that brand image, product quality, and trust collectively have a substantial influence on purchase intention. These findings are consistent with previous research, reinforcing the theoretical understanding that purchase intention is shaped by an interrelated combination of cognitive, affective, and behavioral factors. Theoretically, the study contributes to marketing literature by validating the importance of brand image, product quality, and trust in shaping consumer behavior in the skincare industry.